The Effect of Information Quality, System Quality, Ease of Use on User Satisfaction’s Qris (Quick Response Indonesian Standard) in SME’S - Rachmacandrani, Neni; Natsir, Mokhamad; Respati, Harianto; Haryanto, Sugeng; Setiyadi, Sina (Global Health Science Group, 2023)
This study aims to determine the effect of information quality, system quality, and ease of transaction on QRIS user satisfaction in Batik Blimbing Malang MSMEs. The population of this research is consumers of Batik Blimning Malang City who use the QRIS (Quick Response Indonesian Standard) application. The sampling method used in this study was random sampling method, namely by using a simple random sampling technique. The number of samples in this study was 103. The model and data collection used a questionnaire. The analytical method used is multiple regression analysis. The results of the study found that information quality did not significantly influence QRIS user satisfaction. Then, system quality and ease of transaction have a positive and significant effect on satisfaction. Ease of transaction is the most dominant variable affecting user satisfaction.